2012
DOI: 10.1128/aac.00921-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Persister Tolerance

Abstract: ABSTRACTPersisters are dormant phenotypic variants of regular cells that are tolerant to antibiotics and play an important role in recalcitrance of chronic infections to therapy. Persisters can be produced stochastically in a population untreated with antibiotics. At the same time, a deterministic component of persister formation has also been documented in a population of cells with DNA damaged by fluoroquinolone treatment. Expression of the SOS response under these conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
178
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 45 publications
5
178
2
1
Order By: Relevance
“…3d). Factors such as quorum sensing, cell density, nutrient starvation, diauxic carbon source transitions, environmental signals (such as heat shock, oxidative stress and DNA damage) and stringent response pathways contribute to microbial persistence in vitro [54][55][56][57][58][59] . TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…3d). Factors such as quorum sensing, cell density, nutrient starvation, diauxic carbon source transitions, environmental signals (such as heat shock, oxidative stress and DNA damage) and stringent response pathways contribute to microbial persistence in vitro [54][55][56][57][58][59] . TA modules that are upregulated in persisters are terminal effectors of microbial persistence 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect of H 2 S as an iron-sequestering agent seems to coincide with that of superoxide (56). While superoxide can lead to cellular damage and death, its accumulation induces the protective SoxRS and MarRAB regulons (57). Thus, pretreatment with low-to-moderate concentrations of superoxide provides cells a greater ability to cope with subsequent more severe stress and, more importantly, prevents cells from entering programmed cell death (56).…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that paraquat-induced oxidative stress led to an increase in the level of persisters surviving fluoroquinolone antibiotics, but not ampicillin or kanamycin (147). They showed that SoxRS induces overexpression of the AcrAB-TolC MDR pump, which can extrude fluoroquinolones (147).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%